Validation of personal protective equipment ensembles, incorporating powered air-purifying respirators protected from contamination, for the care of patients with high-consequence infectious diseases. (April 2023) - Crook, B.; Bailey, C.; Sykes, A.; Hoyle, M.C.; Evans, C.; Poller, B.; Makison-Booth, C.; Pocock, D.; Tuudah, C.; Athan, B.; Hall, S.
Summary: Background: The UK High-Consequence Infectious Diseases (HCID) Network of high-level isolation units provides care for patients with contact- or airborne-transmissible highly infectious and highly dangerous diseases. In most HCID units, the healthcare workers (HCWs) wear personal protective equipment (PPE) ensembles incorporating a powered air-purifying respirator (PAPR) for head and respiratory protection. Some PAPRs have components worn outside/over other PPE, necessitating decontamination of re-usable elements. Two alternative PAPRs, with all re-usable elements worn under PPE, were trialled in this study. Aim: To undertake scenario-based testing of PAPRs and PPE to determine usability, comfort and ability to remove contaminated PPE without personal cross-contamination. Methods: Trained healthcare volunteers ( N =20) wearing PAPR/PPE ensembles were sprayed with ultraviolet fluorescent markers. They undertook exercises to mimic patient care, and subsequently, after doffing the contaminated PPE following an established protocol, any personal cross-contamination was visualized under ultraviolet light. Participants also completed a questionnaire to gauge how comfortable they found the PPE. Findings and conclusions: The ensembles were tested under extreme 'worst case scenario' conditions, augmented by physical and manual dexterity tests. Participating volunteers considered the exercise to be beneficial in terms of training and PPE evaluation. Data obtained, including feedback from questionnaires and doffing buddy observations, supported evidence-based decisions on the PAPR/PPE ensemble to be adopted by the HCID Network. One cross-contamination event was recorded in the ensemble chosen; this could be attributed to doffing error, and could therefore be eliminated with further practice.